The strength of SiO2 added MgO ceramics to withstand flashover-treeing appearance under electron bombardment in vacuum - Sutjipto, Agus Geter Edy (2004)
To improve insulating capability of magnesia (MgO) ceramics under electron beam bombardment in vacuum, the addition of SiO2 was studied. A scanning electron microscope (SEM) was used as a source of electron beam and vacuum condition. The capability which was represented by a waiting time to appear the first flashover treeing (hereinafter time to flashover treeing / TTF) changed with adding SiO2 to MgO. It was found that increasing SiO2 additions increased the TTF and got its maximum value for 6 wt% additions. From this study when 6 wt% SiO2 added MgO was used, the insulation property of MgO was significantly increased 5.5 times of withstanding the appearance of first flashover. From three terminals method, it was found that the 6 wt% SiO2 added MgO had the lowest surface conductivity.